Influence of Physical Activity in Children and Adolescents with Cerebral Palsy: A Systematic Review - Faustino Andrés-Pérez; Lluna Maria Bru-Luna; Sergio Hidalgo-Fuentes; Fátima Llamas-Salguero; Manuel Martí-Vilar (Children, 2025)
Cerebral palsy (CP) is one of the most common disorders in childhood that significantly impacts quality of life. Background/Objectives: This study conducted a literature review of physical activity (PA)-based interventions for children and adolescents with CP, highlighting the physical, cognitive, and social benefits, as well as the factors and barriers that influence practice. Methods: The PRISMA methodology was used to identify and analyze the most relevant studies up to December 2024 through specific search equations and the databases Science Direct, Scopus, and Dialnet. Of the 707 articles identified, a total of 62 publications were selected for further analysis. These were subjected to a quality assessment through a checklist based on seven items. Results: The practice of PA guaranteed improvements in balance, postural control, strength, socialization, and self-confidence. On the other hand, some programs, such as Makey Makey, Ballet, aquatic PA, and Matrogymnasia, among others, were highlighted because they promoted an increase in physical practice among the population. However, there are still some barriers, such as sedentary lifestyles (90%), limited accessibility, and a lack of qualified professionals that hinder the intervention and ensure motivation and interest in its practice for those individuals who have not yet begun to practice it. Conclusions: PA is an effective tool to favor quality of life in children and adolescents, as it contributes to their integral development and social inclusion. The need for interdisciplinary strategies to reduce barriers and increase the benefits of PA is emphasized. A joint effort to promote integration in leisure time could promote optimal long-term results.